Surgery for women with endometrioma prior to in vitro fertilisation: proposal for a feasible multicentre randomised clinical trial in the UK. Issue 3 (6th June 2020) - Maheshwari, Abha; Healey, Jemma; Bhattacharya, Siladitya; Cooper, Kevin; Saraswat, Lucky; Horne, Andrew W; Daniels, Jane; Breeman, Suzanne; Brian, Kate; Burns, Gwenda; Hudson, Jemma; Gillies, Katie
Abstract: STUDY QUESTION: Is it feasible to undertake a randomised controlled trial to establish whether surgical removal of endometrioma or not, improves live birth rates from IVF? SUMMARY ANSWER: A randomised controlled trial (RCT) comparing surgery versus no surgery to endometrioma prior to IVF is only feasible in UK if an adaptive rather than traditional study design is used; this would minimise resource wastage and complete the trial in an acceptable time frame. WHAT IS KNOWN ALREADY: There is wide variation in the management of endometriomas prior to IVF, with decisions about treatment being influenced by personal preferences. STUDY DESIGN, SIZE, AND DURATION: This was a mixed-methods study consisting of an online survey of clinicians, a focus group and individual interviews with potential trial participants. PARTICIPANTS/MATERIALS, SETTING, METHODS: Endometriosis and fertility experts across the UK were invited to participate in an online anonymised questionnaire. Potential future trial participants were recruited from a tertiary care fertility centre and invited to participate in either individual interviews or focus groups. MAIN RESULTS AND THE ROLE OF CHANCE: Clinicians and potential trial participants confirmed the need for an RCT to inform the management of an endometrioma prior to IVF. There were 126 clinicians who completed the survey, and the majority (70%) were willing to recruit to a trial. Half of those who responded indicated that they see at least 10 eligible women each year. The main barriers to recruitment were waiting lists for surgery and access to public funding for IVF. One focus group ( n = 7) and five interviews were conducted with potential trial participants ( n = 3) and their partners ( n = 2). The findings from these discussions highlighted that recruitment and retention in a potential RCT could be improved by coordination between IVF and surgical services such that an operation does not delay IVF or affect access to public funding. Live birth was considered the most important outcome with an improvement of at least 10% considered the minimum acceptable by both patients and clinicians. LIMITATIONS, REASONS FOR CAUTION: This feasibility study captured views of clinicians across the UK, but as patients were from a single Scottish centre, their views may not be representative of other areas with limited public funding for IVF. WIDER IMPLICATIONS OF THE FINDINGS: There is a need for an appropriately powered RCT to establish whether or not surgical treatment of endometrioma prior to IVF improves live birth rates. There are logistical issues to be considered due to limited number of participants, funding of IVF and waiting times. These could be overcome in a RCT by using an adaptive design which would include a prospectively planned opportunity for modification of specified aspects of the study design based on interim analysis of the data, coordination of IVF treatments and endometriosis surgeries and international collaboration. Similar principles could be used for other questions in fertility where a traditional approach for randomised trials is not feasible. STUDY FUNDING/COMPETING INTEREST(S): Funding was received from the NHS Grampian R&D pump priming fund (RG14437-12). S.B. is Editor-in-Chief of HROPEN, and A.W.H. is Deputy Editor of HROPEN. Neither was involved in the review of this manuscript. L.S. reports grants from CSO and NIHR to do endometriosis research, outside the submitted work. K.C. reports grants from NIHR/HTA and CSO during the conduct of the study. J.H.e., A.W.H., J.D., S.B.r., K.B., G.B., J.H.u. and K.G. report no conflict of interest.